2004
DOI: 10.1046/j.1600-0749.2003.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Tanning Devices – Fast Track to Skin Cancer?

Abstract: The use of UVB and/or UVA emitting devices for cosmetic tanning is widespread in Western populations including young people and is especially prevalent in females. Several epidemiological studies, although not all, have shown a significant relationship between the use of tanning devices and malignant melanoma after, in some cases, adjustment for confounding factors such as solar ultraviolet radiation (UVR) exposure. A relationship between solar exposure, especially intermittent exposure, and malignant melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…Other advantages of a melanoma action 5 G. Bernhard, personal communication; http://www.libradtran.org/. (20), its use in providing valuable information on the in vivo absorption spectrum of the principal target molecule involved in the UV initiation of melanoma aiding in its identification (1), and its use in suggesting molecular/genetic pathways for future study. These data would provide significant insight into an overall evaluation of the role of UV in melanoma risk.…”
Section: Resultsmentioning
confidence: 99%
“…Other advantages of a melanoma action 5 G. Bernhard, personal communication; http://www.libradtran.org/. (20), its use in providing valuable information on the in vivo absorption spectrum of the principal target molecule involved in the UV initiation of melanoma aiding in its identification (1), and its use in suggesting molecular/genetic pathways for future study. These data would provide significant insight into an overall evaluation of the role of UV in melanoma risk.…”
Section: Resultsmentioning
confidence: 99%
“…Of course it is also possible the larger OR may be the result of small numbers or simply an artifact, which we were unable to assess. A number of epidemiologic investigations have attempted to determine the nature of the putative association between artificial UV and melanoma with more recent studies generally suggesting use of artificial tanning devices is a risk factor [25,28,29]. However, three recent European studies reported conflicting results; the U.K. and multi-center European case-control studies found no association and the only cohort study to date in Scandinavia found the highest association among the youngest users with the longest lag time [26,32,59].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of artificial sources of UV on risk of melanoma has been examined by numerous studies (for example [24][25][26][27][28]) although findings to date have been heterogeneous, with much of the inconsistency attributed to small sample sizes with low statistical power to detect a plausible association [7,[25][26][27][29][30][31][32][33][34][35][36][37][38][39]. Moreover, most studies to date have not been able to distinguish exposures by device type and many did not control for known melanoma risk factors such as pigmentary characteristics and solar exposures [29,37,40].…”
Section: Introductionmentioning
confidence: 99%
“…Because by its nature, exposure to artificial UV radiation through sunlamp and sunbed use is intermittent in character, there has been consistent concern over the past 15 years that use of such devices for recreational tanning may increase risk of melanoma (3). In addition, data from surveys conducted in Europe (4,5) and North America (6) indicate that sunbeds are now being used by an increasing proportion of the population, particularly young people.…”
Section: Introductionmentioning
confidence: 99%